Pendampingan Pembuatan Nomor Induk Berusaha (NIB) Melalui Online Single Submission (OSS) dan Rebranding Bagi Pelaku Usaha Mikro di Desa Bulu Kediri - Imma Rokhmatul Aysa; Sutantri Sutantri (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
The national economy in Indonesia is currently increasing, especially in the Small, Micro and Medium Enterprises (MSME) sector. In the business process, obtaining a permit is considered very important. For micro business actors, having legality is a necessity and a necessity for the continuity of their business. There are approximately 10 MSMEs in Bulu Village, but these actors do not yet have an NIB (Business Identification Number). Apart from that, there are many business actors who have not branded their products with name labels. The implementation of service activities is divided into 4 stages, firstly conducting observations, secondly providing counseling about the importance of NIB and product rebranding, thirdly implementing activities, and finally evaluation. NIB's mentoring services and product rebranding for micro-entrepreneurs in Bulu Village provide positive benefits. Initially they thought that arranging a business permit was complicated, long and expensive, but after receiving assistance they understood that the procedure for obtaining an NIB permit is very easy through OSS and there are many benefits for business actors who have labeled their products so that they are more widely known by relevant consumers. quality, composition, brand, production code and legality